Changes in Minimum Criminal Sanctions for Corruption Offenses in the National Criminal Code Based on the Perspective of the Purpose of Punishment - Imelia Damai Agusthin; Muhammad Azil Maskur (Law Research Review Quarterly, 2025)
The National Criminal Code brings about a paradigm shift in punishment from retributive justice to restorative justice, which emphasizes recovery. Through the process of recodification of criminal law, a number of provisions on corruption in the Anti-Corruption Law were revoked and re-regulated in the National Criminal Code. However, the new regulations have sparked debate due to changes in the minimum prison sentence. There are concerns that this change will weaken the severity of criminal punishment for corruption, which has been understood as a crime that harms the public interest. Based on this background, this paper examines the factors behind the changes to the minimum criminal sanctions for corruption in the National Criminal Code and analyzes these changes from the perspective of the objectives of criminal punishment in Indonesia. This study uses the normative legal research method (doctrinal research) with a statute approach and a conceptual approach. The results of the discussion show that the changes in minimum criminal sanctions were driven by a number of factors, including philosophical, sociological, and juridical factors. The objectives of punishment in the National Criminal Code are aimed at protecting the community and rehabilitating perpetrators, the changes to the minimum penalties for corruption, although designed to create balance, tend to shift the focus towards rehabilitation, thereby risking weakening the protection of society if not accompanied by the recovery of state losses, the application of additional sanctions, consistency in verdicts, and improvements to the rehabilitation system, which still faces structural and cultural problems.